2021
DOI: 10.25259/jsstd_38_2020
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional measles, mumps, and rubella vaccine for the treatment of recalcitrant warts: A case series and review of literature

Abstract: Objectives: To document the response of recalcitrant warts to intralesional measles, mumps, and rubella (MMR) vaccine. Materials and Methods: This case series reports the treatment response to intralesional MMR vaccine observed in 11 patients who attended the dermatology outpatient department with recalcitrant warts of more than 1 year duration. Only the largest wart was treated in each case. The intralesional treatment was repeated at an interval of 2 weeks. Results: Nine patients (81.9%) showed complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…With immunotherapy becoming a favorable treatment option, a number of injectable agents had been employed in wart therapy such as measles, mumps, and rubella vaccine (MMR) and bacillus Calmette‐Guerin vaccine (BCG), and skin test antigens such as the candida antigen and purified protein derivatives (PPD). Immunotherapeutics for warts are thought to induce a delayed hypersensitivity reaction that induces the immune system to recognize and eradicate the causative virus not only at the site of injection but throughout the whole body 3 …”
Section: Introductionmentioning
confidence: 99%
“…With immunotherapy becoming a favorable treatment option, a number of injectable agents had been employed in wart therapy such as measles, mumps, and rubella vaccine (MMR) and bacillus Calmette‐Guerin vaccine (BCG), and skin test antigens such as the candida antigen and purified protein derivatives (PPD). Immunotherapeutics for warts are thought to induce a delayed hypersensitivity reaction that induces the immune system to recognize and eradicate the causative virus not only at the site of injection but throughout the whole body 3 …”
Section: Introductionmentioning
confidence: 99%
“…e authors concluded that zinc oxide ointment can serve as adjunctive therapy to increase the efficacy of other modalities of treatment. [13] A case series on recalcitrant cutaneous warts treated with intralesional MMR vaccine reported complete response in nine of the eleven treated (81.9%), which was comparable to the 82% complete clearance reported by Chauhan et al [30,31] In an open, uncontrolled trial with intralesional vitamin D3 therapy in cutaneous warts, 78.5% of patients had complete resolution. [32] In a 2 year study of cutaneous warts treated with intralesional Candida antigen, 80% of patients showed complete clearance of lesions.…”
Section: Immunotherapy For Wartsmentioning
confidence: 65%